Individuals with substance use disorders experience an increased urge to move to complex music - Jan Stupacher; Benedetta Matarrelli; Danilo Cozzoli; Mario Ventura; Francesco Montinaro; Luciana de Gennaro; Peter Vuust; Elvira Brattico (Proceedings of the National Academy of Sciences, 2025)
Substance use disorders disrupt the dopaminergic system of the human brain, which plays a central role in movement and reward processing, altering perception, and cognition. The pleasurable urge to move to music, known as groove, relies on dopamine for reward, anticipation, beat perception, and motor system activity. Using a well-established paradigm, which shows an inverted-U relationship between groove and musical complexity, we investigated how dopamine downregulation from long-term cocaine and heroin use affects the experience of music. Drug users experienced stronger groove with high rhythmic and harmonic complexities than nonusers, while moderate complexities elicited similar responses across groups. This pattern differs from other populations with altered dopaminergic function, such as Parkinson’s disease or musical anhedonia, highlighting a distinct effect of drug addiction on music perception. The findings suggest that drug users seek more intense and complex stimulation, supporting the hypothesis that a hypodopaminergic state associated with drug use raises the threshold for nondrug stimuli to engage the reward system.